Pengaruh Model Pembelajaran Treffinger Terhadap Kemampuan Berpikir Kreatif Peserta Didik pada Materi Gelombang Bunyi - Sutrisno Sutrisno; Kartika Hajati; Muhammad Zulfikar Abubakar (Kappa Journal, 2025)
Type of this research is quasi-experimental researh with nonequivalent control group design. Purpose of this research was to determine the effect of Treffinger learning model on students’ creative thinking skills in soundwave material in class XI science major MAN 1 Majene. Data collection techniques through creative thinking ability test instruments. Data were analyze with the n-gain descriptive statistical approach and inferential parametric statistics using t-test. The result of this research showed there was significant difference between the two class groups with collective n-gain distribution index for experimental class is 0.81 in the high category and 0.65 in the control class in medium category. The results of the t hypothesis test show that there is an influence of the Treffinger learning model on the creative thinking ability in soundwave material in class XI science major MAN 1 Majene. Future research can broaden the study by applying this model to various educational levels or by comparing it with other creative learning models to examine its relative effectiveness. In addition, further studies are needed to explore students’ affective aspects and scientific process skills as the impact of the sustainable implementation of the Treffinger model.